2022
DOI: 10.3390/asi5050090
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Web Technology and IoT to Contribute to the Management of Blood Banks in Developing Countries

Abstract: Health-care-sector-related activities are more accessible and faster as a result of technological development. Technology such as the Internet of Things (IoT) can work with blood bank services to manage and provide healthy blood in emergencies. However, there are many problems in blood bank management and inventory monitoring, especially in developing countries as compared to developed ones. The lack of an adequate and safe blood supply is a major limitation to health care in the developing world. The instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Furthermore, it's worth noting that enhanced utilization of EHR systems and their delegation were found to be independently associated with heightened levels of physician productivity [16]. Web-based technology and the use of Internet of Things (IoT) sensors can help improve healthcare data management, considering satisfaction, effectiveness, and efficiency [17]. The hypothesis suggested that those maintaining paper-based records or not storing any data might encounter challenges in history taking "(5) Every time".…”
Section: Observation 3: Only 481% Physicians Use Digital Medical Historymentioning
confidence: 99%
“…Furthermore, it's worth noting that enhanced utilization of EHR systems and their delegation were found to be independently associated with heightened levels of physician productivity [16]. Web-based technology and the use of Internet of Things (IoT) sensors can help improve healthcare data management, considering satisfaction, effectiveness, and efficiency [17]. The hypothesis suggested that those maintaining paper-based records or not storing any data might encounter challenges in history taking "(5) Every time".…”
Section: Observation 3: Only 481% Physicians Use Digital Medical Historymentioning
confidence: 99%
“…Remote data access through a web server is provided for medical personnel. The authors of [50] propose a new web-based system that employs IoT sensors for the monitoring of inventories related to blood storage. The structure and typical procedures of a blood bank are presented, optimal storage temperatures are discussed, and steps for process optimizations by means of the proposed system are suggested.…”
Section: Introductionmentioning
confidence: 99%
“…S.Kiruthika monitors the temperature on the blood bank and integrates it with IOT which is displayed on the web. In this study it is possible to identify the blood supply that can be accessed from the blood donation center displayed on the web page [14] [15].…”
Section: Introductionmentioning
confidence: 99%